Männlichkeiten in der Literatur: Konzepte und Praktiken zwischen Wandel und Beharrung - Tholen, Toni (transcript, 2015)
What is the status of the »new man«? The literature since the late 1960s reflects in diverse ways the difficult transformation of concepts of masculinity in solitary and familial ways of life.